STRATEGI PENERAPAN LAYANAN KEUANGAN DIGITAL UMKM PADA USAHA MIE PEDAS HAJI SLAMET - Murhayani Murhayani; Silvia Silvia; Dwi Epty Hidayaty (PT Naureen Digital Education, 2023)
This research aims to determine the development and progress of MSMEs through digitalization of financial services. Experience from various economic crises teaches entrepreneurs that micro, small and medium enterprises (MSMEs) act as the backbone and buffer that actually saves a person from various economic problems. Various breakthroughs and innovations should be made so that the existence of MSMEs is better able to compete so that they have a superior position in the era of information and technological advances. Towards digital transformation, the development of the current time has brought about rapid changes. One of them, is the digitalization of financial services. in the current era of digitalization, everything has switched to an online pattern, namely all applications. This means that the digitalization era is now an important role in the business world in all sectors of life.